MODEL REGULATION FOR DATA PRIVACY IN THE APPLICATION OF BIOMETRIC SMART CARD - Dewi, Sinta (Faculty of Law, Universitas Brawijaya, 2017)
This article discusses the extent to which the use of biometric smart card as a tool to exercise the identification has been increasingly utilized due to its advantages, such as ability to achieve a high level of accuracy, the system cannot be easily duplicated as well as high level of security, since it involves biological characteristics like fingerprints, iris and DNA. Notwithstanding the foregoing, the use of this technology has raised many concerns with regard to the need of privacy data protection. It is due to the fact that biometrics technology as a powerful identifier brings along personal information that can be traced from different sources to be linked together, and also the ability of third parties to access this data in identifiable form and link to other informations and used this information for secondary uses without the consent of data subject. Data privacy is considered as fundamental human rights and has been regulated in a number of international instruments as well as regional instruments and has been incorporated into more than 100 national laws. Countries have now recognized data privacy either as an explicit constitutional rights, or in the form of comprehensive data privacy law. This article will explore data privacy model regulation which is intended to regulate and protect data privacy. This regulatory model combining several approaches in managing data privacy, especially in using biometric smardcard. Firstly, through laws that enforces the principles and international standards. Secondly, through the market approach (market-based solution) which is derived through industry associations to help protect consumer data privacy by applying privacy policy in the form of a statement that the industry will protect consumers' privacy by implementing fair information principles. Third, through technological approach such as PET's (privacy enchasing technology), i.e the techniques for anonymous and pseudo-anonymous payment, communication, and web access. Fourthly, through corporate privacy rules.